An Examination of Social Media as a Medium for Islamic Da'wah: The Role of YouTube as a Da'wah Strategy - Romadlany, Zakiyah; Effendi, Muhammad (Journal of Educational Management Research, 2025)
This research aims to examine the role of YouTube as a medium for Islamic da’wah and its effectiveness in reaching diverse audiences through varied content strategies. With the rapid expansion of digital platforms, YouTube has become a critical tool in spreading Islamic teachings to a global audience. The research uses a qualitative approach, employing content analysis and interviews with content creators and viewers. The findings reveal that YouTube’s accessibility allows for the widespread distribution of da’wah content, reaching Muslims worldwide at any time. The study also identifies that diverse content strategies, including traditional lectures and creative visuals, significantly enhance viewer engagement, especially among younger audiences. However, the research also highlights challenges in ensuring the accuracy of content and preventing misinformation. The implications suggest that while YouTube is a powerful tool for da’wah, stricter oversight and content monitoring are essential. Future research should explore the effectiveness of other social media platforms and examine long-term viewer engagement.